Rancang Bangun Virtual Reality Tour Pengenalan Sekolah Berbasis Web - Fatimah, Dini Destiani Siti; Pariyatin, Yeni; Fhadillah, Shelly Umayah (Jurnal Algoritma, 2025)
Virtual reality tour is a technology that allows users to interact with the virtual world, which is a visualization of the real environment presented online. in the field of education this technology can be used to introduce schools by providing visual experiences including being able to see locations with a 360o view, the use of Virtual Reality Tour technology can be used as a solution as a supporting technology for promotion and introduction at a school. With the Virtual Reality Tour users can see by not coming directly to the School. To build a Web-Based School Introduction Virtual Reality Tour Application implements the Multimedia Development Life Cycle (MDLC) development method with six stages, namely concept, design, material collection, manufacture, testing, and distribution. This research produces a web-based school introduction virtual reality tour application. Beta testing obtained results in accordance with expectations. As well as testing the results of beta testing using the usability testing method with a total of 20 respondents who produced a score of 4.52, this includes very good measured on a scale of 1 to 5.